2008
DOI: 10.1029/2008wr006950
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale particle image velocimetry for measurements in riverine environments

Abstract: [1] Large-scale particle image velocimetry (LSPIV) is a nonintrusive approach to measure velocities at the free surface of a water body. The raw LSPIV results are instantaneous water surface velocity fields, spanning flow areas up to hundreds of square meters. Measurements conducted in typical conditions in conjunction with appropriate selections of parameters for image processing resulted in mean velocity errors of less than 3.5%. The current article reviews the background of LSPIV and the work of three resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
301
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(310 citation statements)
references
References 31 publications
5
301
0
4
Order By: Relevance
“…In the literature, Polatel [30] found that the velocity index ranges from 0.789 to 0.928 based on a series of laboratory experiments. Besides, Muste et al [10] reported that the velocity index is dependent on the vertical profile of velocity affected by flow aspect ratio, Froude and Reynolds number, micro and macro bed roughness, and relative submergence of large-scale roughness elements. Le Coz et al [20] utilized LSPIV approach to measure flash floods, giving a velocity index of 0.90 based upon available gauging data.…”
Section: Comparison Surface Velocity and Water Level During Typhoon Ementioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, Polatel [30] found that the velocity index ranges from 0.789 to 0.928 based on a series of laboratory experiments. Besides, Muste et al [10] reported that the velocity index is dependent on the vertical profile of velocity affected by flow aspect ratio, Froude and Reynolds number, micro and macro bed roughness, and relative submergence of large-scale roughness elements. Le Coz et al [20] utilized LSPIV approach to measure flash floods, giving a velocity index of 0.90 based upon available gauging data.…”
Section: Comparison Surface Velocity and Water Level During Typhoon Ementioning
confidence: 99%
“…In recent years, non-intrusive approaches based on radar (e.g., [5]) and/or imaging systems (e.g., [6][7][8][9][10][11][12][13][14][15][16]) have been increasingly applied, providing a safer alternative for measuring flood discharge. Without the needs of human-operated physical sampling and data acquisition, surface velocities are characterized from continuous images of observed (seeded fluid) flows mainly using two types of algorithms, i.e., particle tracers and imagine analyses (e.g., [17]).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a larger amount of data, three consecutive time series were recorded from a fixed position leading to a total of 60 images. This drawback of the camera could be circumvented by using a (high frame rate) video camera instead of a photo camera (Bradley et al 2002;Meselhe et al 2004;Muste et al 2008). During the image recording, the parameters controlling the visualization and illumination of the seeding particles are critical (Stanislas & Monnier 1997).…”
Section: Image Recordingmentioning
confidence: 99%
“…To correct the perspective distortion due to the angle between the optical axis of the camera and the plane of the image, orthorectification is required (Creutin et al 2003;Muste et al 2008). In this case, image orthorectification was avoided by placing the optical axis perpendicular to the field of view.…”
Section: Image Recordingmentioning
confidence: 99%
“…New technologies have been developed for discharge and surface velocity measurements due to concerns about flow conditions, costs, accuracy, inaccessible locations, measuring time and the safety of conventional methods. One emerging technology is large-scale particle image velocimetry (LSPIV), which has several advantages over conventional measurement techniques; namely, LSPIV is safer, non-intrusive and provides continuous measurements [5].…”
Section: Introductionmentioning
confidence: 99%